2019
DOI: 10.1038/s41598-019-48830-w
|View full text |Cite
|
Sign up to set email alerts
|

Energetic electron assisted synthesis of highly tunable temperature-responsive collagen/elastin gels for cyclic actuation: macroscopic switching and molecular origins

Abstract: Thermoresponsive bio-only gels that yield sufficiently large strokes reversibly and without large hysteresis at a well-defined temperature in the physiological range, promise to be of value in biomedical application. Within the present work we demonstrate that electron beam modification of a blend of natural collagen and elastin gels is a route to achieve this goal, viz. to synthesize a bioresorbable gel with largely reversible volume contractions as large as 90% upon traversing a transition temperature that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Therefore, it seems that neither the network percolation nor the bundling is the main effector for the nonlinear response but that it is most likely EBI-related chemical changes. In previous work, electron beam-treated keratin and elastin–collagen gels exhibited a reduction in the α-helical content with a concomitant increase in β-sheet and random coil, respectively [ 30 , 34 ]. This unfolding was conceptualized before as the origin of strain stiffening; furthermore, studies on hard keratin, keratin-like bundles, and vimentin (another IF protein) have confirmed the loss of the α-helical structure and the creation of an extended β-sheet upon stretching [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems that neither the network percolation nor the bundling is the main effector for the nonlinear response but that it is most likely EBI-related chemical changes. In previous work, electron beam-treated keratin and elastin–collagen gels exhibited a reduction in the α-helical content with a concomitant increase in β-sheet and random coil, respectively [ 30 , 34 ]. This unfolding was conceptualized before as the origin of strain stiffening; furthermore, studies on hard keratin, keratin-like bundles, and vimentin (another IF protein) have confirmed the loss of the α-helical structure and the creation of an extended β-sheet upon stretching [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method is reagent-free, with no potentially toxic residual reagents, making it very useful for cell studies. Additionally, it has been shown to be a convenient tool for a systematic tuning of the material properties in biopolymer networks [ 28 , 29 , 30 , 31 , 32 ]. The formation of stable covalent crosslinks between polymer chains through irradiation gives rise to a significant increase in the storage modulus of irradiated gels.…”
Section: Introductionmentioning
confidence: 99%
“…Altered elastin content, as well as crosslinking differences of the lungs in preterm infants compared to adults may serve as a key role in the observed mechanical differences (Chrzanowski et al, 1980;Mižíková and Morty, 2015). Moreover, as shown by Wilharm et al (2019), buckling instabilities such as Euler buckling in elastin networks, can enforce structural failure (Han et al, 2013;Nelson, 2016), and the network collapses irreversibly under a certain load. Such behavior is not seen in our experiments since the tissue is most likely stabilized by incompressible cells, which, in case of tissue compression, impede a network collapse.…”
Section: Discussionmentioning
confidence: 99%
“…[1,37] Therefore, ELPs, RLPs, and SLPs show promising potential in drug delivery, incremental expression and purification of engineered proteins, ameliorating biosecurity and usage as protein-based medicines. [38][39][40][41] Transient receptor potential vanilloid 1 (TRPV1) is the founding member of thermosensitive transient receptor potential (TRP) channels in mammals to respond to ambient temperature by changing Ca 2 + permeability, which was first reported by Caterina et al in 1997. [42,43] TRPV1 consists of tetrad monomeric subunits arrayed in a four-fold symmetry around the ion path center.…”
Section: Thermal-responsive Proteinsmentioning
confidence: 99%
“…By tuning the LCST, the polypeptides will be phase‐separated or self‐assemble into nanoparticles or micelles [1,37] . Therefore, ELPs, RLPs, and SLPs show promising potential in drug delivery, incremental expression and purification of engineered proteins, ameliorating biosecurity and usage as protein‐based medicines [38–41] …”
Section: Natural Proteins With Physical Stimuli‐responsive Propertiesmentioning
confidence: 99%